Teologi Perdamaian dalam Tafsîr Jihad - Wasid Wasid (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2011)
The presence of Islam within humanity's space would, in fact, lead to the creation of life in order to fulfill tawhîd and peace of the world. The problem of tawhîd is the very core of life, though its meaning has, sometimes, tended to be theocentric by neglecting the anthropocentric dimension. It can be observed through the ideological reasoning of radicalism group in defining jihâd as a means of struggle to uphold God's oneness. However, this group put less interested in presenting Islam within principles of peace. It suggests that God's oneness (tawhîd) is purely intended to Him, and it has no relation with a human. This problem needs to be re-observed, if not to be sued, by looking at universal values from Islam's presence. It has been so far known as highly honoring peace and values of humanity and values of divinity.